2014
DOI: 10.2147/cmar.s65444
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial fluid flow in cancer: implications for disease progression and treatment

Abstract: As cancer progresses, a dynamic microenvironment develops that creates and responds to cellular and biophysical cues. Increased intratumoral pressure and corresponding increases in interstitial flow from the tumor bulk to the healthy stroma is an observational hallmark of progressing cancers. Until recently, the role of interstitial flow was thought to be mostly passive in the transport and dissemination of cancer cells to metastatic sites. With research spanning the past decade, we have seen that interstitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
185
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 110 publications
3
185
0
Order By: Relevance
“…During glioma progression, alterations in ECM and elevated hypoxia signaling lead to a compromised and leaky vasculature with poor perfusion. As extracellular fluid accumulates, interstitial fluid pressures can rise dramatically (Alberti et al, 1978;Kullberg and West, 1965;Narayan et al, 1982;Stocchetti and Maas, 2014) and, as this fluid moves down its pressure gradient, into the healthy brain, local increases in fluid shear forces are experienced by tumor cells (Munson and Shieh, 2014). Increased fluid pressure causes tissue compression, which leads to increased migration and transcriptional changes in cancer cells (Butcher et al, 2009).…”
Section: Effects Of Mechanical Changes On Glioma Progressionmentioning
confidence: 99%
“…During glioma progression, alterations in ECM and elevated hypoxia signaling lead to a compromised and leaky vasculature with poor perfusion. As extracellular fluid accumulates, interstitial fluid pressures can rise dramatically (Alberti et al, 1978;Kullberg and West, 1965;Narayan et al, 1982;Stocchetti and Maas, 2014) and, as this fluid moves down its pressure gradient, into the healthy brain, local increases in fluid shear forces are experienced by tumor cells (Munson and Shieh, 2014). Increased fluid pressure causes tissue compression, which leads to increased migration and transcriptional changes in cancer cells (Butcher et al, 2009).…”
Section: Effects Of Mechanical Changes On Glioma Progressionmentioning
confidence: 99%
“…From an electrical point of view, these junctions contribute to increasing the sensitivity of the tissue to an externally applied electric field. However, from a medical point of view, these interactions can provide important information on tissue health because some diseases related to cell necrosis and/or degeneration (e.g., cancer) can lead to serious deterioration of these interstitial spaces [38,39].…”
Section: Biological Tissuesmentioning
confidence: 99%
“…8). Both experimental and theoretical studies have shown that IFP is elevated in the tumors of patients with cancer, and whereas little TIF is found in the tumor interior, it is primarily present near the tumor boundary (9). TIF originates from blood plasma that extravasates from the capillaries through pores and intercellular clefts in the vessel wall.…”
Section: Introductionmentioning
confidence: 99%